155k views
4 votes
F(x)=9x^3+2x^2-5x+4 and g(x)=5x^3-7x+4 what isf(x)-g(x)

1 Answer

4 votes
Answer:
f(x) - g(x) = 4x³ + 2x² + 2x

Step-by-step explanation:
We are given that:
f(x) = 9x³ + 2x² - 5x + 4
g(x) = 5x³ - 7x + 4

We want to get the value of f(x) - g(x). This means that we will simply subtract g(x) from f(x) as follows:
f(x) - g(x) = 9x³ + 2x² - 5x + 4 - (5x³ - 7x + 4)
f(x) - g(x) = 9x³ + 2x² - 5x + 4 - 5x³ + 7x - 4
f(x) - g(x) = 9x³ - 5x³ + 2x² - 5x + 7x + 4 - 4
f(x) - g(x) = 4x³ + 2x² + 2x

Hope this helps :)
User Gennady Kandaurov
by
6.2k points